Analogue-digital ASICs circuit techniques, design tools and applications - Soin, Randeep Singh 1952-; Maloberti, F. (Franco); Franca, José (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1991)
The book comprises 18 chapters dealing with the following subjects: technology and modeling aspects of an advanced BiCMOS ASIC process; high performance operational amplifiers and comparators; switched capacitor filters; switched current techniques for analogue sampled data signal processing; data converters; oversampling converters; self-callibrating and algorithmic converters; a high flexibility BiCMOS standard cell library for mixed analogue-digital ASICs; practical aspects of mixed analogue-digital design; some applications of mixed signal ASICs; a video communication application of an analogue-digital ASIC; high level simulation and hardware description languages; circuit level/gate level mixed-mode simulation; testing mixed analogue-digital circuits; towards high level synthesis of mixed signal ASICs; automated high level synthesis of data conversation; and automated analogue design.